El Excentrico, 1972-01-20 - Garcia, Humberto:::Publisher:::::::::::: (Garcia Printing; San Jose, California, 2023)
January 20, 1972 [20 de enero de 1972]. No volume or issue number. Cover has a photograph of Mexican actress Maria Victoria in formal wear.